A Measurement Study of the Structured Overlay Network in P2P File-Sharing Systems. (30th August 2007) - Zhou, Mo; Dai, Yafei; Li, Xiaoming
Abstract : The architecture of P2P file-sharing applications has been developing to meet the needs of large scale demands. The structured overlay network, also known as DHT, has been used in these applications to improve the scalability, and robustness of the system, and to make it free from single-point failure. We believe that the measurement study of the overlay network used in the real file-sharing P2P systems can provide guidance for the designing of such systems, and improve the performance of the system. In this paper, we perform the measurement in two different aspects. First, a modified client is designed to provide view to the overlay network from a single-user vision. Second, the instances of crawler programs deployed in many nodes managed to crawl the user information of the overlay network as much as possible. We also find a vulnerability in the overlay network, combined with the character of the DNS service, a more serious DDoS attack can be launched.